2003
DOI: 10.1046/j.1469-8137.2003.00848.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid composition of Botrytis cinerea and inhibition of its radiolabelling by the fungicide iprodione

Abstract: Summary• Botrytis cinerea is an important plant pathogen that causes grey mould in over 200 hosts. It is often controlled by dicarboximides, which have various proposed mechanisms of action, including effects on lipids. Here we have examined the effect of one dicarboximide, iprodione, on lipid metabolism.• B. cinerea , cultured in malt extract media, was challenged with iprodione and its lipids extracted, separated by TLC, and analysed by GLC. Lipid metabolism was followed using [1-14 C]acetate.• Triacylglycer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…These are rich in PC and PE phospholipids but also ergosterol (ERGO). Phosphatidylinositol (PI) is often present, followed by PS, and it is generally found in the outer leaflet of fungal membranes, whereas in mammalian cells, it is mostly located in the inner leaflet [ 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. With the exception of PC, CXJ interacts efficiently with bilayer composed of the most common fungal phospholipids: PE ( Figure 3 F, Figure 5 B and Figure 6 B) and PI ( Figure 3 K and Supplementary Figure S7 ), partially conserving the U-shaped structure ( Figure 4 F).…”
Section: Resultsmentioning
confidence: 99%
“…These are rich in PC and PE phospholipids but also ergosterol (ERGO). Phosphatidylinositol (PI) is often present, followed by PS, and it is generally found in the outer leaflet of fungal membranes, whereas in mammalian cells, it is mostly located in the inner leaflet [ 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. With the exception of PC, CXJ interacts efficiently with bilayer composed of the most common fungal phospholipids: PE ( Figure 3 F, Figure 5 B and Figure 6 B) and PI ( Figure 3 K and Supplementary Figure S7 ), partially conserving the U-shaped structure ( Figure 4 F).…”
Section: Resultsmentioning
confidence: 99%
“…In the HPh diet, linoleic acid was supplied by a wheat germ (0.49%) and sunflower oil (0.12%), while it was only present in the maize oil (0.05%) in the LPh diet. The 4% B. cinerea that was added to the LPh diet provided around 0.06% linoleic acid (Griffiths et al, 2003), so this could have partially compensated for a possible shortage of this fatty acid in this diet. Even the data of Mondy and Corio‐Costet (2000) suggested that the positive effect of B. cinerea on L. botrana performance should not be attributed exclusively to fungal sterols.…”
Section: Discussionmentioning
confidence: 99%
“…The important role of this fatty acid in Lepidoptera, both for adult emergence and normal larval growth and development, has been demonstrated (Beenakkers, Van Der Horst, & Van Marrewijk, 1985; Canavoso & Wells, 2001; Dadd, 1983). Linoleic acid is present in grapevine berries (around 0.96 mg/g dry weight both in the skin and pericarp; Miele, Bouard, & Bertrand, 1993) and in B. cinerea as well (around 13.6 mg/g dry weight; Griffiths, Dancer, O'Neill, & Harwood, 2003). In the HPh diet, linoleic acid was supplied by a wheat germ (0.49%) and sunflower oil (0.12%), while it was only present in the maize oil (0.05%) in the LPh diet.…”
Section: Discussionmentioning
confidence: 99%
“…Lipids were extracted from freshly harvested spores obtained from cultures grown on PDA according to Griffiths et al (2003). Dried spores were transferred to test tubes and extracted with hot 2-propanol (70 uC, 3 ml).…”
Section: Synthesis Of Cyclopentenone Compounds (8)mentioning
confidence: 99%
“…Hot 2-propanol was used to extract the lipids as it inactivates lipid-degrading enzymes which can yield artefactual results (Griffiths et al, 2003). Palmitate (16 : 0), stearate (18 : 0), oleate (18 : 1 n-9), linoleate (18 : 2 n-6) and a-linolenate (18 : 3 n-3) were detected in varying proportions in all fungal spores, with 18 : 2 (n-6) being the major component in all species (Table 1).…”
Section: Lipid Composition Of Fungal Sporesmentioning
confidence: 99%